Motif Structure and the Liminal Function of Death in The Milk-White Doo, A Scottish Folktale - Alvanita, Alvanita (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2025)
Although Scottish folktales form part of the broader European tradition, they remain underrepresented in global folklore studies. Meanwhile, Scottish tales are rich with cultural traditions and national identity, which tend to be marginalized by the British tales. This article examines the portrayal of death in The Milk-White Doo, a Scottish fairy tale, using an interdisciplinary approach that combines folkloristics and literary analysis. Drawing on the Thompson Motif-Index, Propp’s Morphology of the Folktale, and Victor Turner’s theory of liminality, the study identifies four dominant motifs: unnatural cruelty, animal transformation, reincarnation, and reward and punishment. In addition, it also discusses how death functions structurally through the narrative roles of absentation, villainy, victory, and wedding. The analysis highlights how death is depicted not as an end, but as a liminal process marked by separation, transition, and incorporation. This transformation serves to restore moral and familial order, which reflects historical beliefs in death as a just consequence for wrongdoing. By situating death within a ritual and symbolic framework, the study contributes to broader discussions on justice, grief, and renewal in folklore. It also encourages further research into how modern adaptations reshape traditional death motifs to align with modern cultural values.